ANALYSIS QUALITY SOIL FROM THE ASPECT OF APPLICATION SIMULTANEOUS POTENTIOMETRIC STRIPPING ANALYSIS - Ljiljana Babincev; Dejan Gurešić; Aleksandra Perić-Grujić; Ljubinka Rajaković (Journal of Engineering & Processing Management, 2013)
The research described in this paper is directed towards the development and application of simultaneous potentiometric stripping analysis for the determination of heavy metals (lead, cadmium and zinc) in the soil of the northern part of the territory of Kosovo and Metohija. The experiments were carried out: I) the module solution (prepared from standard solutions of metal working and deionized water), II) in the soil samples. The selected two types of land: agricultural (location next to the road in the vicinity of industrial areas) and non-agricultural (parks and playgrounds). To that end are analyzed, compared and separated optimum parameters: The working electrode is formed by depositing layer of mercury on glassy carbon with a constant stream of -49.90 μA, pH 1.6 and time deposit with a 240 s from a solution of mercury(II) nitrate. The extracting of metals from solution was performed at pH 2.1 and the potential of -1.400 V. Soil samples are after the drying, homogenisation and sifting translated in solution by dissolving with concentrated nitric and hydrochloric acid. The results of this study revealed are deviations for: lead -4.58%, cadmium -1.91% and zinc -1.89%. Was found that landfills mining Kombinat Trepca have a significant influence on the quality of the soil. Was found that mining landfills of Trepca have a significant influence on the quality of the soil. The highest content of investigated metals were found in soils in the immediate proximity passive and active mining landfills. Content of investigated elements, on almost all measuring places along the road, have had values above the maximum allowable.
Keywords: lead; cadmium; zinc; soil; potentiometric stripping analysis